2003
DOI: 10.1093/ps/82.3.360
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of bacitracin methylene disalicylate when fed in combination with narasin in the management of necrotic enteritis in broiler chickens

Abstract: The efficacy of bacitracin methylene disalicylate (BMD) in the management of necrotic enteritis (NE) when fed in combination with narasin was investigated in a floor-pen study of 2,000 broiler chickens using a Clostridium perfringens inoculum challenge model. Treatments consisted of 1) nonchallenged-nonmedicated; 2) challenged-nonmedicated; 3) challenged-narasin (70 ppm); 4) challenged-BMD (55 ppm); 5) challenged-narasin (70 ppm) + BMD (55 ppm). Medication was provided in the feed from Day 0 to trial terminati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
7

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 6 publications
2
28
0
7
Order By: Relevance
“…The counts of C. perfringens in luminal contents from the ileum and caeca of birds fed the PC diet were as low as 3-4 log 10 cfu/g digesta on both sampling days, indicating that the IFAs used in the present study were highly effective in controlling C. perfringens proliferation in the gut of broilers. These findings are consistent with previous studies of the culture-based and molecular studies, which demonstrated that dietary supplementation with antibiotics such as Zn-bacitracin, bacitracin methylene disalicylate and tylosin causes a significant reduction in lesion scores and mortality caused by NE (Brennan et al 2003;Collier et al 2003).…”
Section: Ileal and Caecal Microflorasupporting
confidence: 92%
“…The counts of C. perfringens in luminal contents from the ileum and caeca of birds fed the PC diet were as low as 3-4 log 10 cfu/g digesta on both sampling days, indicating that the IFAs used in the present study were highly effective in controlling C. perfringens proliferation in the gut of broilers. These findings are consistent with previous studies of the culture-based and molecular studies, which demonstrated that dietary supplementation with antibiotics such as Zn-bacitracin, bacitracin methylene disalicylate and tylosin causes a significant reduction in lesion scores and mortality caused by NE (Brennan et al 2003;Collier et al 2003).…”
Section: Ileal and Caecal Microflorasupporting
confidence: 92%
“…Most of the beneficial effects of AGPs are linked to the reduced incidence of subclinical infections (George et al, 1982;Snyder and Wostmann, 1987;Brennan et al, 2003). Furthermore, stability of the microbial ecology by AGPs has been reported to alleviate problems associated with microbial production of toxins including the thinning of the intestinal wall, suppression of inflammation, and the reduction of bioamines and toxins produced by bacteria (Feighner and Daskevicz, 1987;Knarreborg et al, 2004).…”
Section: Antimicrobial Propertiesmentioning
confidence: 99%
“…Avoparcin reduced the numbers of C. perfringens in the intestinal tract of broilers and prevented necrotic enteritis in broilers, challenged with C. perfringens type A (Prescott, 1979;Elwinger et al, 1998). Although many C. perfringens poultry isolates appear to be resistant against bacitracin (Kondo, 1988;Devriese et al, 1993;Watkins et al, 1997), inclusion of this agent in broiler feed reduced intestinal C. perfringens counts, the number of gut lesions, lesion scores and mortality caused by necrotic enteritis in challenge experiments and field trials (Prescott, 1979;Stutz et al, 1983;Stutz & Lawton, 1984;Broussard et al, 1986;Engberg et al, 2000;Lovland et al, 2003;Brennan et al, 2003;Jackson et al, 2003). Also multiple studies showed that tylosin (Stutz & Lawton, 1984;Vissiennon et al, 2000;Brennan et al, 2001;Collier et al, 2003) and virginiamycin (George et al, 1982;Stutz & Lawton, 1984) inclusion in broiler feed reduced the occurrence of and mortality due to necrotic enteritis, and the intestinal counts of C. perfringens.…”
Section: Growth-promoting Antibioticsmentioning
confidence: 99%